DRG payment for major pancreatic surgery: analysis of resource consumption and suggestions from a tertiary hospital in China - Hou, Rui; Liu, Xiaokun; Zhou, Jingya; Zhang, Taiping; Wang, Weibin; Zhu, Weiguo (Frontiers in Public Health, 2024)
Aim To investigate the cost homogeneity within the Diagnosis-Related Group (DRG) “major operation of pancreas and liver, with general complications or comorbidities” (HB13), its cost-influencing factors, and to propose suggestions for better grouping efficacy. Methods Medical and insurance settlement data of inpatients covered by the DRG payment system at the author’s institution were collected from March 15, 2022 to December 31, 2023. The cost homogeneity of group HB13 was assessed using the coefficient of variation (CV). Clinical factors that may have an impact on hospitalization cost for patients undergoing pancreatic surgery were identified through a semi-structured interview administered to the pancreatic surgeons in author’s department, their significance was analyzed using multiple linear regression, along with their impact on the cost of different service categories. A proposal to subdivide HB13 was made and evaluated by CV and t-test. Results The CV of the HB13 group was 0.4. Robotic-assisted surgery and pancreaticoduodenectomy were two independent factors that significantly affected the total cost. Patients undergoing robotic-assisted surgery have an average increase of 41,873 CNY in total cost, primarily derived from operation fee. Patients undergoing pancreaticoduodenectomy have an average increase of 37,487 CNY in total cost, with significant increases across all service categories. HB13 was subdivided based on whether pancreaticoduodenectomy was performed. The newly formed groups exhibited lower CVs than the original HB13. Conclusion The cost homogeneity of HB13 was lower than that of other DRG groups in author’s department. It is recommended to introduce a supplementary payment for patients requiring robotic-assisted surgery, to guarantee their access to this advanced technology. It is recommended to establish a new group with higher payment standard for patients undergoing pancreaticoduodenectomy. A tiered CV criterion for the evaluation of grouping efficacy is recommended to increase intra-group homogeneity, facilitating a better allocation of health insurance funds, and the prevention of unintended negative outcomes such as service cuts and cherry-picking.